2017
DOI: 10.1039/c6nr09477e
|View full text |Cite
|
Sign up to set email alerts
|

Polarity and growth directions in Sn-seeded GaSb nanowires

Abstract: We here investigate the growth mechanism of Sn-seeded GaSb nanowires and demonstrate how the seed particle and its dynamics at the growth interface of the nanowire determine the polarity, as well as the formation of structural defects. We use aberration-corrected scanning transmission electron microscopy imaging methodologies to study the interrelationship between the structural properties, i.e. polarity, growth mechanism, and formation of inclined twin boundaries in pairs. Moreover, the optical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…Here we just mention that the liquid droplet catalyzing the VLS growth of any NWs should wet the growth front but not the NW sidewalls. 26,28,36 In general, (111)A facets are rarely seen as the growth front in a nanowire. One reason could be that their surface energy would be higher than for (111)B and hence their formation would be energetically and geometrically suppressed in favor of the (111)B facets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we just mention that the liquid droplet catalyzing the VLS growth of any NWs should wet the growth front but not the NW sidewalls. 26,28,36 In general, (111)A facets are rarely seen as the growth front in a nanowire. One reason could be that their surface energy would be higher than for (111)B and hence their formation would be energetically and geometrically suppressed in favor of the (111)B facets.…”
Section: Resultsmentioning
confidence: 99%
“…Another recent study showed similar results on Sn-seeded GaSb NWs. 28 In this case, the A-polar NWs were defect-free, in contrast to the B-polar NWs which had spaced stacking defects appearing in the <111>A direction. The presence of these defects resulted in zigzag-shaped sidewalls in B-polar NWs.…”
Section: Introductionmentioning
confidence: 88%
“…For example, Au has been considered as a universal catalyst for the growth of 1D nanostructures [55,99,100]. However, once Au is doped into Si NWs, it forms fatal defects quickly and deteriorates electrical properties of Si NWs, making it incompatible with CMOS technique [101,102]. On the other hand, Pd, a CMOS-compatible metal [103,104], readily forms palladium silicide (Pd 2 Si) when it is doped into the Si NW, which is a compound commonly employed as an electrical contact of Si devices.…”
Section: The Fundamental Properties and Growth Mechanism Of Sb-based mentioning
confidence: 99%
“…This three-fold symmetry can be related to the surface polarity (polarity is the internal electric field of the crystal caused by the asymmetry in the charge distribution of a cation-anion bond in tetrahedrally coordinated compound semiconductors such as III-V and II-VI. 32 The terminating element at the surface determines the surface polarity). The GaAs stem forms side facets from the {112} family which are semi-polar planes: three of them are A-polar while the other three are B-polar.…”
Section: Takedownmentioning
confidence: 99%